2001
DOI: 10.1161/01.hyp.37.2.334
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of 12(S)-HETE in Patients With Essential Hypertension

Abstract: Abstract-The platelet-type 12-lipoxygenase (12-LO) catalyzes the transformation of arachidonic acid into 12-hydroperoxyeicosatetraenoic acid [12-(S)HPETE], which is reduced to 12-hydroxyeicosatetraenoic acid [12-(S)HETE]. These metabolites exhibit a variety of biological activities such as mediation of angiotensin II-induced intracellular calcium transients in cultured rat vascular smooth muscle cells. It has recently been reported that platelet 12(S)-HETE production is enhanced in the spontaneously hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 28 publications
3
64
1
Order By: Relevance
“…6A Inset). The production of 12-HETE after BK application was also confirmed by an enzyme immunoassay by using a polyclonal antibody specific to 12(S)-HETE (14). As shown in Fig.…”
Section: Resultsmentioning
confidence: 61%
“…6A Inset). The production of 12-HETE after BK application was also confirmed by an enzyme immunoassay by using a polyclonal antibody specific to 12(S)-HETE (14). As shown in Fig.…”
Section: Resultsmentioning
confidence: 61%
“…As previously shown, Ang II increases 12-LO expression (Natarajan et al, 1993;Kim et al, 1995). The activities of 12-LO and the 12-LO metabolite 12(S)-hydroxyeicosatetraenoic acid (12(S)-HETE) are increased in SHR, and many studies have demonstrated a role for 12-LO and 12(S)-HETE in the pathogenesis of experimental and Ang II-induced hypertension (Sasaki et al, 1997;González-Núnez et al, 2001) and in cytokine-induced VSMCs migration and proliferation (Natarajan et al, 1997). In the present study, we demonstrated the inhibitory action of CCL5 on Ang II-induced 12-LO mRNA expression and production via AT2 receptor in SHR VSMCs.…”
Section: Discussionmentioning
confidence: 92%
“…Increased levels of 12(S)-HETE have been observed in hypertensive and diabetic patients (50,51). The LO pathway has been implicated in the oxidation of low density lipoprotein to its atherogenic form and in the pathogenesis of atherosclerosis (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%